System Development for Geolocation in Harsh Environments - Joana Maria Serra Enes (2018)
Wireless sensor networks (WSN) consist of a set of distributed devices equipped with multiple sensors, which can be employed in different environments of varying characteristics. Nowadays, node localization has become one of their most basic and important requirements. Due to the nature of certain environments, typical positioning systems, such as Global Navigation Satellite System (GNSS), cannot be employed. Therefore, in recent years several alternative positioning mechanisms have risen. ROMOVI is a project which has as its main goal the development of low cost autonomous robots capable of monitoring and perform logistic tasks on the steep slopes of the Douro river vineyards. Integrated in this project, this dissertation proposes the development of a full-custom wireless communication system for geolocation purposes in harsh environments. Using a Symmetric Double Sided Two Way Ranging (SDS-TWR) algorithm, it is possible to achieve ranging measures between nodes, thus providing accurate relative positioning. This work focuses mainly on the study of the SDS-TWR algorithm and its major error sources, such as those due to digital clock drift, among others. A preamble based on Frank-Zadoff-Chu sequence was developed and, due to its good periodic autocorrelation properties, a system employing the transmission and reception of this preamble was implemented in hardware, through a field programmable gate array (FPGA). By employing an embedded logic processor, the Altera Nios II, control over the complete procedure of the aforementioned algorithm is possible, to perform and analyze the main advantages of the SDS-TWR algorithm. Finally, a medium access control (MAC) layer frame format was defined, in order to enable future development of communication among multiple nodes, to enhance the original algorithm and, as such, provide the capability of trilateration.